STUDI KUALITAS PUPUK NITROGEN (N), FOSFOR (P) DAN KALIUM (K) YANG DIJUAL DI BEBERAPA TOKO PERTANIAN DI KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Tobing, Laurensius; Lucky, Maylani (University of Prof. Dr. Hazairin, SH, 2024)
The sale of low-quality fertilizers is very detrimental to farmers and the government because it can thwart farmers' harvests and at the same time can also thwart government programs such as the National Rice Production Improvement Program (P2BN) and the Food Security and Resilience Program. This study was conducted to determine the quality of N, P and, K fertilizers sold to the public at agricultural shops in Sekadau Hilir District, Sekadau Regency. In this study, 4 fertilizer samples were taken, consisting of: NPK Mutiara 16:16:16 fertilizer, Mutiara brand, NPK 16:16:16 fertilizer, PT Bumi Gemilang Artha, NPK 13:6:27 fertilizer, PT Bumi Gemilang Artha, and NPK 16:16:16 fertilizer Pak Tani. The results of the fertilizer sample analysis showed that NPK 16:16:16 Mutiara fertilizer contains 14% N, 22.65% P205 and, 17.69% K2O and the NPK 16:16:16 Pak Tani fertilizer sample contains 12.36% N, 5.70% P205 and 28.50% K2O which have very good quality. Still, there are also examples of NPK 16:16:16 27 PT Bumi Gemilang Artha fertilizer containing 2.36% N, 2.14% P205 and, 0.06% K2O and the NPK 13:6:27 PT Bumi Gemilang Artha fertilizer sample contains 0.26% N, 2.30% P205 and 0.26% K2O which are of poor quality.